2022
DOI: 10.1186/s13567-022-01099-w
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of peste des petits ruminants vaccine seed “45G37/35-k”, Russia

Abstract: Production of peste des petits ruminants (PPR) vaccines in Russia is based on two attenuated virus strains (“45G37/35-k” and “ARRIAH”) of common origin. Here, the identity of the strain PPRV/45G37/35-k was investigated using a full genome, Illumina deep sequencing approach. Phylogenomic analysis showed that PPRV/45G37/35-k belongs to the same lineage as the widely used PPRV vaccine strain Nigeria/75/1 (lineage II). However, 248 nucleotide differences separate the genomes of these vaccine strains, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The ARRIAH strain produced by FGBI ARRIAH belongs to lineage II, as the Nigeria 75-1 vaccine strain does, but is not directly related to the wild Nigeria strain at the origin of this vaccine [ 26 ]. Although it still lacks WOAH endorsement, this vaccine has been used in some central Asian countries to control PPRV spread [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ARRIAH strain produced by FGBI ARRIAH belongs to lineage II, as the Nigeria 75-1 vaccine strain does, but is not directly related to the wild Nigeria strain at the origin of this vaccine [ 26 ]. Although it still lacks WOAH endorsement, this vaccine has been used in some central Asian countries to control PPRV spread [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that a PPRV vaccine strain, 45G37-k (Pokrov, Russia), differed from Nigeria75/1 by 248 nucleotides; however, the ARRIAH strain was related to 45G37-k, indicating the shared origin. These lineage II variants likely originated from a distinct lineage II field isolate that circulated alongside the predecessor of Nigeria 75/1 in the past [ 26 ]. Although Nigeria 75/1 was attenuated on 75 passages in Vero cells [ 20 ], the attenuating mutations accrued during this passage history differ from those of the ARRIAH and 45G37-k strains (35 passages in lamb kidney cells for ARRIAH and serial passages in lamb kidneys, lamb testes, and Saiga kidney cells for 45G37-k) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPRV genome analyses have also been important in exploring the origin and the attenuation process of PPR vaccine strains ( Eloiflin et al. 2019 ; Kwiatek et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%